Traumatic Birth Experience with Cesarean Section and Breastfeeding Outcomes - OROVOU, EIRINI; Eskitzis, Panagiotis; Antoniou, Evangelia (International Journal of Innovative Research in Medical Science, 2022)
Introduction A perinatal factor that appears to be highly correlated with postpartum PTSD is breastfeeding. There are several researchers who have studied the traumatic experience of birth and its impact on breastfeeding. More specifically, Türkmen in 2020 [1] reported a high correlation between Post Traumatic Stres Disorder (PTSD), traumatic perception of childbirth and low breastfeeding self-efficacy. According to the authors, the most important reason for low breastfeeding rates in PTSD postpartum women is the increased cortisol secretion, which suppresses oxytocin production resulting in reduced milk production. In another recent study published in 2018 [2], it is equally argued that postpartum PTSD can negatively affect the initiation and maintenance of lactation. It is a fact that a traumatic birth experience can create difficulties in breastfeeding from the beginning, and even undermine it completely. For example, in another study, mothers who had a complicated vaginal delivery or an Emergency Cesarean Section (EMCS) were more likely to suffer from PTSD and breastfeeding difficulties [3]. A possible explanation for this phenomenon was attempted by Beck in 2011 [4], describing how breastfeeding after a traumatic birth experience can trigger flashbacks to the traumatic birth and ultimately act as a deterrent to breastfeeding in the mother trying to avoid mental pain.